PHYSICO CHEMICAL ANALYSIS OF POLLUTED POUND WATER - JITENDRA KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
The unquenchable need for information and the insatiable human curiosity that drives it are the key basis upon which the expansion of scientific knowledge is constructed. An important percentage of the progress that has been accomplished in scientific research and technological practice has been directed toward the manufacture or development of human comforts, which has led to an overall improvement in the standard of living in the community. This chapter includes a literature review that is relevant to the objective of the study, which is to determine the current state of water quality. The purpose of the research is to determine the current state of water quality. In addition to that, information on the production of adsorbents and the ways in which they may be used to purge impurities from water is included in this chapter. It has been said that a considerable amount of effort has been done to improve the water quality, the production of a number of adsorbents, and the use of those adsorbents in order to get rid of the sulfur-containing pesticide. In addition, this report contains a condensed explanation of the different adsorbents that may be used to remove the toxins from the environment. In addition to that, we have included a discussion on the most recent thinking about the quality of the water that is available to those who live in rural regions.